1993
DOI: 10.1128/aem.59.7.2244-2250.1993
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformations of ferulic acid by Saccharomyces cerevisiae and Pseudomonas fluorescens

Abstract: Saccharomyces cerevisiae (dry baker's yeast) and Pseudomonasfluorescens were used to convert trans-ferulic acid into 4-hydroxy-3-methoxystyrene in 96 and 89% yields, respectively. The metabolites were isolated by solid-phase extraction and analyzed by thin-layer chromatography and high-performance liquid chromatography. The identities of the metabolites were determined by 'H-and "3C-nuclear magnetic resonance * Corresponding author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(41 citation statements)
references
References 27 publications
0
40
0
1
Order By: Relevance
“…Thus, although yeast is not a lignin-degrader, it might contain a class of enzymes involved in the last steps of the lignin biodegradation pathway, which deal with single monomers produced by the catabolic process. The recent discovery that S. cerevisiae produces a decarboxylase that converts two major lignin derivatives, trans-ferulic and p-coumaric acid, to vinylguaiacol and vinylphenol, respectively, is also consistent with this hypothesis (Huang et al, 1993). Furthermore, our knowledge of yeast secondary metabolism is very limited and, so, there is a good chance that a significant fraction of yeast genes of unknown function may play a role in such a process.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus, although yeast is not a lignin-degrader, it might contain a class of enzymes involved in the last steps of the lignin biodegradation pathway, which deal with single monomers produced by the catabolic process. The recent discovery that S. cerevisiae produces a decarboxylase that converts two major lignin derivatives, trans-ferulic and p-coumaric acid, to vinylguaiacol and vinylphenol, respectively, is also consistent with this hypothesis (Huang et al, 1993). Furthermore, our knowledge of yeast secondary metabolism is very limited and, so, there is a good chance that a significant fraction of yeast genes of unknown function may play a role in such a process.…”
Section: Introductionmentioning
confidence: 64%
“…These data encouraged us to investigate a possible role for S. cerevisiae in the degradation of low molecular weight aromatic compounds arising from the degradation of natural biopolymers such as lignocellulose. Recently, it was discovered that yeast is able to produce specific decarboxylases that are able to attack trans-ferulic and p-coumaric acid (the main constituents of the lignin macromolecule; Huang et al, 1993). In addition a gene, PAD1, able to confer the resistance to the cinnamic acid, has been cloned (Clausen et al, 1994).…”
Section: Reduction Of Veratraldehyde To Veratryl Alcohol In Yeast Stamentioning
confidence: 99%
“…It can be used to produce vanillin through biotransformation in micro-organisms. Major pathways from four different initial reactions have been proposed: (i) b-oxidation of substitued cinnamic acids in Rhodotorula rubra (Huang et al 1993); however, no experimental evidence exists to support this hypothesis, (ii) a nonoxidative process via feruloyl-CoA, which further undergoes hydratation to vanillin and acetyl-CoA (Overhage et al 1999), (iii) the reduction of ferulic acid to dihydroferulic acid, which leads to the formation of vanillic acid and subsequently to vanillin (Lesage-Meesen et al 1999), (iv) the nonoxidative decarboxylation of ferulic acid observed in many bacteria (Labuda et al 1992) particularly in the wine LAB (Cavin et al 1993). This last pathway involves the elimination of one carbon to form 4-vinylguaiacol.…”
Section: Discussionmentioning
confidence: 99%
“…94,95 Many studies have been conducted in order to create value-added products based on biotransformation of ferulic acid. 96 Sutherland et al 93 reported that microorganisms such as Streptomyces setonii are responsible for the metabolism of vanillin production from ferulic acid. In recent years, increasing market demand for natural flavours has shifted the industry towards vanillin production from natural resources through a biotechnological approach.…”
Section: Ferulic Acidmentioning
confidence: 99%